Microbiological Contamination of the Office Environment in Dental and Medical Practice - Alexandre Baudet; Monique Guillaso; Léonie Grimmer; MEDIQAI Study Group; Marie Regad; Arnaud Florentin (MDPI AG, 2021)
The microbiological contamination of the environment in independent healthcare facilities such as dental and general practitioner offices was poorly studied. The aims of this study were to describe qualitatively and quantitatively the bacterial and fungal contamination in these healthcare facilities and to analyze the antibiotic resistance of bacterial pathogens identified. Microbiological samples were taken from the surfaces of waiting, consulting, and sterilization rooms and from the air of waiting room of ten dental and general practitioner offices. Six surface samples were collected in each sampled room using agar contact plates and swabs. Indoor air samples were collected in waiting rooms using a single-stage impactor. Bacteria and fungi were cultured, then counted and identified. Antibiograms were performed to test the antibiotic susceptibility of bacterial pathogens. On the surfaces, median concentrations of bacteria and fungi were 126 (range: 0-1280) and 26 (range: 0-188) CFU/100 cm2, respectively. In indoor air, those concentrations were 403 (range: 118-732) and 327 (range: 32-806) CFU/m3, respectively. The main micro-organisms identified were Gram-positive cocci and filamentous fungi, including six ubiquitous genera: Micrococcus, Staphylococcus, Cladosporium, Penicillium, Aspergillus, and Alternaria. Some antibiotic-resistant bacteria were identified in general practitioner offices (penicillin- and erythromycin-resistant Staphylococcus aureus), but none in dental offices. The dental and general practitioner offices present a poor microbiological contamination with rare pathogenic micro-organisms.